Peningkatan Kemampuan Pemecahan Masalah Matematis dan Kemandirian Belajar Siswa melalui Pembelajaran Penemuan Terbimbing Di Kelas VII Mts Alwashliyah Gedung Johor - Ramadhani, Ramadhani; Dalimunthe, Irma Ramayani (Jurnal Absis: Jurnal Pendidikan Matematika dan Matematika, 2021)
This study aims to improve students' mathematical problem-solving abilities and self-regulated learning through guided discovery learning for class VII students of MTs Alwashliyah Gedung Johor Medan. This research is an experimental study with a pretest-posttest design. The population in this study were all class VII students, totaling 42 students. The instrument used is a mathematical problem-solving ability test and a learning independence questionnaire. This study indicates that the average value of the initial test of problem-solving ability is 43.05, and the average value of the final test of learning independence is 57.55. The average value of the initial questionnaire for learning independence was 63.88, and the average value of the final questionnaire was 70.76. The results of the Mathematical Problem Solving Ability test's hypothesis test with t-count = 10,073 and t-table = 1,66 so that t-count > t-table. The Independent Learning Questionnaire hypothesis results with t-count = 3.53 and t-table = 1.66 so that t-count > t-table. The result shows that Ho is rejected and Ha is accepted, which means that there is an increase in mathematical problem-solving abilities and student learning independence through guided discovery learning before and after being given treatment.